Quantitative analysis of melamine in food contact materials by using high-performance liquid chromatography - Lapviboonsuk, Jutathip; Lapviboonsuk, Sompop (Bulletin of Applied Sciences, 2015)
Melamine food contact materials are produced from melamine resin or melamine-formaldehyde occurring from the polymerization reaction of melamine and formaldehyde. The residuals of melamine from FCMs can contaminate foods. European Union has issued Commission Regulation (EU) No 1282/2011 about specific migration limit (SML) of melamine (2.5 mg/kg). Therefore, this research studied the migration test method of melamine from food contact materials using 3% acetic acid and high performance - liquid chromatography (HPLC). The suitable extraction method was the use of 70 °C for 2 hours. This migration method was verified and found 2-80 mg/kg linearity range, 0.60 mg/ kg limit of detection (LOD) and 2.00 mg/kg limit of quantitation (LOQ). Accuracy expressed as %recovery and precision expressed as %relative standard deviation (RSD) as well as uncertainty value conformed to the acceptable criteria of test method for food contact materials: EUR 24105 EN: 2009. Moreover, the melamine wares were collected from local markets in Bangkok, Thailand; the amounts of melamine in samples were tested and ranged from not detected to 15.3 mg/kg.